MicroRNA‐338‐5p reverses chemoresistance and inhibits invasion of esophageal squamous cell carcinoma cells by targeting Id‐1. Issue 12 (17th November 2019) - Han, Liang; Cui, Di; Li, Bin; Xu, Wen Wen; Lam, Alfred King Y.; Chan, Kin Tak; Zhu, Yun; Lee, Nikki P.Y.; Law, Simon Y.K.; Guan, Xin Yuan; Qin, Yan Ru; Chan, Kwok Wah; et al.
Abstract: 5‐Fluorouracil (5‐FU) is a chemotherapeutic agent commonly used to treat esophageal squamous cell carcinoma (ESCC), but acquisition of chemoresistance frequently occurs and the underlying mechanisms are not fully understood. We found that microRNA (miR)‐338‐5p was underexpressed in ESCC cells with acquired 5‐FU chemoresistance. Forced expression of miR‐338‐5p in these cells resulted in downregulation of Id‐1, and restoration of both in vitro and in vivo sensitivity to 5‐FU treatment. The effects were abolished by reexpression of Id‐1. In contrast, miR‐338‐5p knockdown induced 5‐FU resistance in chemosensitive esophageal cell lines, and knockdown of both miR‐338‐5p and Id‐1 resensitized the cells to 5‐FU. In addition, miR‐338‐5p had suppressive effects on migration and invasion of ESCC cells. Luciferase reporter assay confirmed a direct interaction between miR‐338‐5p and the 3′‐UTR of Id‐1. We also found that miR‐338‐5p was significantly downregulated in tumor tissue and serum samples of patients with ESCC. Notably, low serum miR‐338‐5p expression level was associated with poorer survival and poor response to 5‐FU/cisplatin‐based neoadjuvant chemoradiotherapy. In summary, we found that miR‐338‐5p can modulate 5‐FU chemoresistance and inhibit invasion‐related functions in ESCC by negatively regulating Id‐1, and that serum miR‐338‐5p could be a novel noninvasive prognostic and predictive biomarker in ESCC. Abstract : We found that microRNA (miR)‐338‐5p was underexpressed in esophageal squamous cell carcinoma cells with acquired 5‐fluorouracil (5‐FU) chemoresistance, and that reexpression of miR‐338‐5p could resensitize them to 5‐FU treatment through targeting Id‐1. MicroRNA‐338‐5p was significantly downregulated in tumor tissue and serum of patients with esophageal squamous cell carcinoma. Low serum miR‐338‐5p was predictive of poor response to 5‐FU/cisplatin‐based neoadjuvant chemoradiotherapy.